2022
DOI: 10.1021/jacs.2c03546
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachlorophthalimides as Organocatalytic Acceptors for Electron Donor–Acceptor Complex Photoactivation

Abstract: Excitation of photoactive electron donor−acceptor (EDA) complexes is an effective way to generate radicals. Applications in a catalytic regime typically use catalytic donors. Herein, we report that readily available electron-poor tetrachlorophthalimides can act as effective organocatalytic acceptors to trigger the formation of EDA complexes with a variety of radical precursors not amenable to previous catalytic methods. Excitation with visible light generates carbon radicals under mild conditions. The versatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…Recently, Melchiorre and co-workers have reported that readily available electron-deficient tetrachlorophthalimides can act as catalytic acceptors in EDA complex photochemistry for Giese-type reactions . Their strategy is compatible with a variety of radical precursors including dihydropyridines (DHPs), alkylsilicates, and organotrifluoroborates.…”
Section: Eda Complexes With Catalytic Acceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Melchiorre and co-workers have reported that readily available electron-deficient tetrachlorophthalimides can act as catalytic acceptors in EDA complex photochemistry for Giese-type reactions . Their strategy is compatible with a variety of radical precursors including dihydropyridines (DHPs), alkylsilicates, and organotrifluoroborates.…”
Section: Eda Complexes With Catalytic Acceptorsmentioning
confidence: 99%
“…The quantum yield (Φ) of the reaction was measured to be 0.04, consistent with a closed catalytic cycle. The authors were also successful in combining EDA photocatalysis with cobaloxime catalysis to perform Heck-type cross-coupling reactions …”
Section: Eda Complexes With Catalytic Acceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 a ,5 Since 2019, the EDA catalysis strategy, i.e. EDA complex-mediated radical generation with catalytic amounts of electron donors 6–9 or acceptors, 10 has emerged as a rapidly growing subfield. Since the donor or acceptor catalyst functions through the association with leaving group-bearing moieties, the EDA catalysis approach is selective and efficient as was demonstrated in the pioneering studies.…”
Section: Introductionmentioning
confidence: 99%
“…UV-vis studies also demonstrated that an electron donor–acceptor (EDA) complex between the DHP anion and the Michael acceptor was unlikely under our reaction conditions (see ESI†). 24…”
mentioning
confidence: 99%